Intracranial Subdural Hematoma after Spinal Anesthesia for Cesarean Section. (24th December 2013) - Schweiger, Vittorio; Zanconato, Giovanni; Lonati, Gisella; Baggio, Silvia; Gottin, Leonardo; Polati, Enrico
Abstract : Intracranial subdural hematoma following spinal anesthesia is an infrequent occurrence in the obstetric population. Nevertheless, it is a potentially life-threatening complication. In the majority of the cases, the first clinical symptom associated with intracranial subdural bleeding is severe headache, but the clinical course may have different presentations. In this report, we describe the case of a 38-year-old woman with an acute intracranial subdural hematoma shortly after spinal anesthesia for cesarean section. Early recognition of symptoms of neurologic impairment led to an emergency craniotomy for hematoma evacuation with good recovery of neurologic functions. The possibility of subdural hematoma should be considered in any patient complaining of severe persistent headache following regional anesthesia, unrelieved by conservative measures. Only early diagnosis and an appropriate treatment may avoid death or irreversible neurologic damage.